Characterisation of Mn0·7Zn0·3Fe2O4 nanoparticles prepared by two stage annealing. (1st November 2013) - Hamed, A; Fitzgerald, A G; Wang, L Y; Gueorguieva, M; Malik, R; Melzer, A
<x xml:space="preserve">Abstract</x> Nanoparticles of the spinel ferrite Mn0·7Zn0·3Fe2O4, with potential for use as contrast agents for magnetic resonance imaging applications, have been prepared by a sol-gel method followed by a two stage annealing process. The second stage of the annealing process improved the quality of the nanoparticles but also led to intergrown aggregates. The nanoparticles were milled to reduce this aggregation. After hand milling, the average nanoparticle size was 20 nm and after 5 h ball milling, the average nanoparticle size was 10 nm. The principal objectives of this study were to assess the effects of the two stage annealing process and milling on average nanoparticle size, crystal quality and magnetic properties relating to potential use in magnetic resonance imaging. Preliminary cytotoxicity measurements enabled assessment of possible nanoparticle contamination during milling on potential medical and clinical applications. A special surfactant was modified to disperse the nanoparticles in water and render them hydrophilic and to reduce agglomeration.